2016
DOI: 10.1002/aic.15254
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model for real gas flow in shale nanopores with non‐circular cross‐section

Abstract: An analytical model for gas transport in shale media is proposed on the basis of the linear superposition of convective flow and Knudsen diffusion, which is free of tangential momentum accommodation coefficient. The present model takes into the effect of pore shape and real gas, and is successfully validated against experimental data and Lattice-Boltzmann simulation results. Gas flow in noncircular nanopores can be accounted by a dimensionless geometry correction factor. In continuum-flow regime, pore shape ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…A higher Knudsen number indicates the distances between gas molecules are comparable to the pore dimension, resulting in rarefied gas3437, thus more gas production could be obtained. Besides, the slippage effect could accelerate the gas molecules transport speed because there is less drag or no stationary layer to slow them34.…”
Section: Resultsmentioning
confidence: 99%
“…A higher Knudsen number indicates the distances between gas molecules are comparable to the pore dimension, resulting in rarefied gas3437, thus more gas production could be obtained. Besides, the slippage effect could accelerate the gas molecules transport speed because there is less drag or no stationary layer to slow them34.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 also shows that the apparent permeability is high initially, drops steeply with increasing pore pressure, and approaches a constant value at high pore pressure (>5 MPa). This is because, at low pore pressure, the dominant transport mechanism is Knudsen diffusion, which enhances gas transport in shale [40]. With increasing pore pressure, the effect of Knudsen diffusion vanishes, which results in the decrease of the apparent permeability.…”
Section: Model Validation With Experimental Datamentioning
confidence: 94%
“…The Knudsen number for producing shale gas reservoirs is less than unity, which corresponds to the Darcy flow, slip flow, and early transitionflow regimes [39]. In this work, we consider slip flow as a part of Knudsen diffusion [40]. Moreover, we do not consider the surface diffusion in this work.…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that both the type of crosssection and the shape of nanopores affected gas transport capacity. Ren et al (2016) proposed an analytical model for real gas transport in nanopores of shale reservoirs based on the linear superposition of convective flow and Knudsen diffusion. The model was established to be free of tangential momentum accommodation coefficient and taken into the effect of pore shape and real gas.…”
Section: Complicated Models With Different Effects Includedmentioning
confidence: 99%